Prognostic Significance of Lymphovascular Invasion in Clinically Localized Prostate Cancer after Radical Prostatectomy - Dilek Ertoy Baydar; Barbaros Baseskioglu; Haluk Ozen; Pinar Ozdemir Geyik (The Scientific World Journal)
Whether lymphovascular invasion (LVI) is an independent prognostic factor in prostate cancer is still controversial. We retrospectively investigated its predictive role in disease progression following radical prostatectomy. The histological sections of radical prostatectomies from 71 clinically localized, prostatic adenocarcinoma patients were reviewed for LVI. Pre- and postoperative follow-up data were collected. LVI was identified in 15.5% of cases. Univariate analysis showed a significant association between LVI and advanced pathological stage, higher Gleason score, positive surgical margins, extraprostatic extension, seminal vesicle invasion, and lymph node metastasis (each p < 0.05). Multivariate analyses pointed to vascular involvement as a strong and independent predictor for PSA failure (p = 0.023), and reduced biochemical progression-free survival (p = 0.019). LVI in radical prostatectomy is an adverse prognostic finding that must be recorded in the pathology report.